Program KALIMASADA Ciptakan Masyarakat Tertib Administrasi Kependudukan - Uswatun Hasanah; Vidya Imanuari Pertiwi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Residents' awareness of the Population Administration is in fact so minimal that residents decide not to update or update their Population Administration data. In fact, there are not a few residents who admit that they do not have the Population Administration document at all. As a result, residents experience several problems in obtaining other services as an example for residents who live in the city of Surabaya, the phenomenon of inactivity of the BPJS card is a result that has often occurred lately where after further investigation the cause of the deactivation of the BPJS card is administrative data. Residents who show inappropriate domiciles, namely outside the city of Surabaya. Thus the MSIB internship activity was carried out with the aim of conducting a survey as well as door to door outreach regarding the importance of Population Administration data so that it is hoped that it can increase public awareness of their Population Administration data. Survey activities as well as door-to-door socialization are carried out in two ways, namely the pre-implementation and implementation stages.